Predictive model of the relationship between social support, body image perception, and physical activity among university students - Xuejiao, Gao; Xiaolin, Wang; Chen, Soon Chee; Samsudin, Shamsulariffin; Hassan, Muhammad Zarif; Luhong, Ma; Pan, Liu; Yuming, Zhang (Springer Nature, 2025)
This cross-sectional study explored the relationship between social support, body image perception, and physical activity among university students. A total of 400 students (mean age = 20.58, SD = 1.71) from six faculties and departments at Ludong University participated voluntarily, with convenience sampling employed for participant selection. The Multidimensional Social Support Scale, Physical Activity Rating Scale, and Body Image States Scale were administered to assess relevant variables. The results indicated that support from family, friends, and school support, as well as body image perception, were positively associated with university students’ physical activity. Mediation analyses revealed that body image perception partially mediated the relationship between friend support and physical activity and fully mediated the relationship between school support and physical activity. No mediation effect was found between family support and physical activity. These findings suggest that friend and school support play a more prominent role in influencing university students’ physical activity through body image perception. Programs aiming to promote physical activity among university students should prioritize enhancing friend and school support alongside strategies to improve body image perception, ultimately fostering healthier behaviors and overall well-being.